Pengaruh Celebrity Endorser dan Daya Tarik Iklan Terhadap Keputusan Pembelian di UMKM Rimaadeeva Hijab Karawang pada Media Sosial Instagram - Kharisma; Citra Savitri; Syifa Pramudita Faddila (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of Muslim fashion in Indonesia is predicted to become a global center for Muslim fashion, supported by the emergence of various local brands, such as Rimaadeeva Hijab, an MSME from Karawang, as well as the support from local celebrities who are beginning to contribute to the Muslim fashion business. The aim of this research is to investigate and explain the impact of celebrity endorsers and advertising appeal on purchasing decisions in the UMKM Rimaadeeva Hijab located in Karawang. The method employed in this study is a quantitative approach. The sampling technique used is non-probability sampling with a sample size of 392 individuals. Data collection is conducted through the utilization of closed-ended questionnaires. Data analysis is performed using Partial Least Square (PLS) with the aid of SmartPLS application. Based on the hypothesis analysis results, it has been proven that there exists a positive and significant relationship between celebrity endorsers and advertising appeal on purchasing decisions. The implications of these findings are crucial for UMKM Rimaadeeva Hijab to adopt celebrity endorser strategies and enhance advertising appeal, thereby increasing consumers' purchasing decisions towards the offered products.